Boosting Oxygen Evolution Reaction Performance on NiFe-Based Catalysts Through d-Orbital Hybridization - Wang, Xing; Pi, Wei; Hu, Sheng; Bao, Haifeng; Yao, Na; Luo, Wei. (Nano-Micro Letters, 2024)
Anion-exchange membrane water electrolyzers (AEMWEs) for green hydrogen production have received intensive attention due to their feasibility of using earth-abundant NiFe-based catalysts. By introducing a third metal into NiFe-based catalysts to construct asymmetrical M-NiFe units, the d-orbital and electronic structures can be adjusted, which is an important strategy to achieve sufficient oxygen evolution reaction (OER) performance in AEMWEs. Herein, the ternary NiFeM (M: La, Mo) catalysts featured with distinct M-NiFe units and varying d-orbitals are reported in this work. Experimental and theoretical calculation results reveal that the doping of La leads to optimized hybridization between d orbital in NiFeM and 2p in oxygen, resulting in enhanced adsorption strength of oxygen intermediates, and reduced rate-determining step energy barrier, which is responsible for the enhanced OER performance. More critically, the obtained NiFeLa catalyst only requires 1.58 V to reach 1 A cm−2 in an anion exchange membrane electrolyzer and demonstrates excellent long-term stability of up to 600 h. Highlights: 1 The NiFeLa catalyst with 3d-5d orbital coupling exhibits remarkable oxygen evolution reaction (OER) activity and stability, enabling an anion-exchange membrane water electrolyzers device to achieve a cell voltage of only 1.58 V at 1 A cm−2 as well as long-term stability over 600 h. 2 The introduction of La disrupts the symmetry of Ni-Fe units and optimize d band center, which affects the d-p orbital hybridization between the metal sites on the surface of the catalyst and oxygen-containing intermediates during the OER process. 3 The 5d-introduced NiFeLa has enhanced adsorption strength of oxygen intermediates, which can reduce the rate-determining step energy barrier and prevent catalyst dissolution.